Genetic Testing of Children for Predisposition to Mood Disorders: Anticipating the Clinical Issues. Issue 4 (22nd March 2014) - Erickson, Jessica A.; Kuzmich, Lili; Ormond, Kelly E.; Gordon, Erynn; Christman, Michael F.; Cho, Mildred K.; Levinson, Douglas F.
Abstract: Large‐scale sequencing information may provide a basis for genetic tests for predisposition to common disorders. In this study, participants in the Coriell Personalized Medicine Collaborative ( N  = 53) with a personal and/or family history of Major Depressive Disorder or Bipolar Disorder were interviewed based on the Health Belief Model around hypothetical intention to test one's children for probability of developing a mood disorder. Most participants (87 %) were interested in a hypothetical test for children that had high ("90 %") positive predictive value, while 51 % of participants remained interested in a modestly predictive test ("20 %"). Interest was driven by beliefs about effects of test results on parenting behaviors and on discrimination. Most participants favored testing before adolescence (64 %), and were reluctant to share results with asymptomatic children before adulthood. Participants anticipated both positive and negative effects of testing on parental treatment and on children's self‐esteem. Further investigation will determine whether these findings will generalize to other complex disorders for which early intervention is possible but not clearly demonstrated to improve outcomes. More information is also needed about the effects of childhood genetic testing and sharing of results on parent–child relationships, and about the role of the child in the decision‐making process.